Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.6 - Factoring Trinomials - Exercise Set - Page 304: 68



Work Step by Step

The two numbers whose product is $ac= 1(6)=6 $ and whose sum is $b= -5 $ are $\{ -2,-3 \}$. Using these two numbers to decompose the middle term, then the factored form of the expression, $ x^4-5x^2+6 $, is \begin{array}{l}\require{cancel} x^4-2x^2-3x^2+6 \\\\= (x^4-2x^2)-(3x^2-6) \\\\= x^2(x^2-2)-3(x^2-2) \\\\= (x^2-2)(x^2-3) .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.